Optimalisasi Exhaust Brake pada Unit HINO 500 FM 260 JD untuk Menurunkan Potensial Lost Cost Unit Hauling - M.Burhanudin; Harjono, Harjono; Prihadianto, Braam Delfian; Sugiyanto, Sugiyanto (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2025)
Based on field observations, the exhaust brake component on the Hino 500 FM 260 JD unit frequently experiences breakdowns. One of the primary causes of failure is the ingress of mud into the exhaust chamber, which disrupts the functionality of the component. This study aims to compare the performance of exhaust brake components with and without a protective cover to enhance their lifetime, analyze the failure rate, and calculate the potential lost cost associated with exhaust brake failures in hauling units. Data collection was conducted directly in the field, and protective covers were installed on three dump truck units in the hauling fleet. The test results indicate that when the exhaust brake component was used without a cover, 14 failures were recorded, whereas with the cover installed, only 4 failures occurred. These findings demonstrate that the protective cover significantly impacts the lifetime and failure rate of the exhaust brake component. Following the testing phase, a potential lost cost analysis was conducted, considering four cost variables: spare parts, production losses, operator costs, and mechanic costs.